Knowledge, Beliefs and Perception of Leprosy - Nidhi Jaswal; BG Banerjee; Anil K Sinha; Sukhbir Singh (Disability, CBR and Inclusive Development)
Purpose: For intervention to be effective, it is essential that the knowledge, beliefs and perception of a specific social group are taken into account. This is particularly true of leprosy where the problems of social stigma and ostracism are more prominent than the disease itself. There are many misconceptions about the cause, methods of transmission, and treatment. The main objectives of the study were to examine the socio-demographic profile of persons with leprosy and to explore their knowledge, beliefs and perception about the disease and its initial symptoms, within a specific socio-cultural milieu. Method: Semi-structured interviews were held with a persons with leprosy at various clinics and care-homes for affected persons in and around Chandigarh, India. Those who had completed their treatment and those who were still undergoing treatment were included in the study. Data collection was done through case studies and in-depth interviews. Results: The name of the disease varied across different geo-cultural zones. Many respondents who were afflicted with only red patches and had no ulcers, believed that they suffered from a skin disease which would turn into leprosy if proper medication was not received. The perception of 64.9 % of the respondents was that leprosy resulted from supernatural causes like God’s punishment, karma, and sin. Conclusion: There is a need to educate persons with leprosy and their families about the etiology of the disease.